"And Then COVID Hits": A Qualitative Study of How Jails Adapted Services to Treat Opioid Use Disorder During COVID-19. (28th January 2023) - Harrington, Calla; Bailey, Amelia; Delorme, Elizabeth; Hano, Samantha; Evans, Elizabeth A.
Abstract: Background: Jails in Massachusetts are among the first nationwide to provide correctional populations with medications to treat opioid use disorder (MOUD). The COVID-19 pandemic caused jails to pivot and adapt MOUD programming. We aimed to identify adaptations and barriers to MOUD access that COVID-19 exacerbated or created, and document new elements that staff wish to sustain as COVID-19 recedes. Methods : We conducted semi-structured in-depth interviews and focus groups in 2020–2021 with 29 jail staff who implement MOUD programming in two Massachusetts jails. We conducted qualitative data analysis in Atlas.ti 8 using an inductive approach. Results: Participants shared that access to MOUD among correctional populations is understood by jail staff to be an essential health service. Thus, to facilitate continued access to MOUD, both during incarceration and also at community reentry, jail staff quickly implemented changes in MOUD regulations and dosing protocols and established telehealth capacity. Despite these program adaptations, participants identified how COVID-19 increased health and social needs among correctional populations, reduced availability of community-based healthcare and recovery-supportive services, and introduced new factors that could undermine recovery. Innovations that participants wished to sustain as COVID-19 receded included telehealth capacity, smaller-sized therapeutic groups, and application of a public health approach to treat opioid use disorder among correctional populations. Conclusions: During disruptive events, jails can adapt MOUD programming to ensure access for people living in jail and upon release. Findings identify factors for understanding the outcomes of jail-based MOUD programming during COVID-19 and highlight opportunities to improve service delivery after COVID-19.